An investigation into teacher perspectives and experiences in integrating HIV and AIDS information across the curriculum at some selected Junior Secondary Schools in the Oshana Region, Namibia - Shifotoka, Simsolia Namene (Rhodes University, Faculty of Education, Department of Education, 2013)
HIV and AIDS are still among the world's most significant public health challenges. Education is widely regarded as an effective response to the pandemic - a "social vaccine" that can increase young people's awareness of the dangers of HIV infection and thus decrease their vulnerability to HIV and AIDS. Integrating HIV and AIDS awareness across the school curriculum is therefore one of the strategies being implemented to educate learners about the pandemic. There are challenges; however, related to the central goal of integrating HIV and AIDS education and also to the form "“ in particular, the pedagogical practices - that this might best take. This qualitative case study research investigated teachers' perspectives, experiences, and levels of preparedness with regard to integrating HIV and AIDS information in the main carrier subjects, mathematics and geography, in some junior secondary schools in Namibia. The study situates debates on curriculum integration and draws on Fogarty's (1999) models of curriculum integration as a conceptual and analytic tool to examine the nature, form and content of integration. It includes a questionnaire on curriculum integration completed by 53 teachers as well as a component consisting of observations and interviews with four teachers from two schools. The results reveal patterns that also emerge in earlier studies on curriculum integration. This approach is already widely recognized as challenging and problematic in the context of general education. However, this and other studies show that when HIV and AIDS are brought into the arena, additional factors come into play and further complicate the process, because of the sensitivity of this topic. In addition, the task of integrating HIV and AIDS education has been added to an already overcrowded curriculum. Teachers have not been provided with adequate (or any) training with concrete examples that might facilitate their efforts to integrate HIV and AIDS information into subjects like the ones under scrutiny in this study. The picture that emerges from examining the evidence on HIV and AIDS integration against Fogarty's (1991) 10 models of curriculum integration is one in which teaching practices are ad hoc, opportunistic and haphazard right across the sample. The choice of integration models for implementation of the HIV and AIDS component in these subjects has been largely left to the opportunity, ability and personal inclinations of individual teachers. The results point to a range of responses, with many teachers not teaching HIV and AIDS at all or some hesitantly experimenting with different approaches; all to limited effect in realizing the intended national goals of this curriculum project. The overall pattern also reveals a degree of frustration among the teachers in the sample, who acknowledged and were concerned at the enormity of the HIV and AIDS challenge facing the country. They recognised the motive behind the policy to have the education system play an important role in response to the HIV challenge, but felt frustrated with the social, personal and practical difficulties of actually implementing the policy within the context of poor (or no) training, knowledge, and support.
Keywords: AIDS (Disease) -- Prevention -- Study and teaching (Secondary) -- Namibia -- Oshana; HIV infections -- Prevention -- Study and teaching (Secondary) -- Namibia -- Oshana; Mathematics -- Study and teaching (Secondary) -- Namibia -- Oshana; Geography -- Namibia -- Oshana -- Study and teaching (Secondary); Curriculum planning -- Namibia -- Oshana; Teachers -- Namibia -- Attitudes